Central African Republic : Priorities for Ending Poverty and Boosting Shared Prosperity - World Bank Group (World Bank, Washington, DC, 2019)
This Systematic Country Diagnostic is the result of a diagnostic exercise conducted by World Bank staff. It was prepared to inform the strategic dialogue between the Government of the Central African Republic (CAR) and the World Bank about priority areas for World Bank Group engagement. This Systematic Country Diagnostic aims to identify key elements to help the country embark on a path of growth and sustainable poverty reduction and to end the cycle of conflict. The analysis was guided by three questions: (a) How can development initiatives contribute to stabilization and a peaceful resolution of the conflict? (b) How does one deliver public services in a country where state presence is limited? (c) Which investments are critical to kick-starting a process of growth, taking into account regional/geographic variation, low population density, and limited urbanization?